Pengembangan E-Modul Mesin-Mesin Listrik Berbasis Problem Solving - Yoga Pratama; Hansi Effendi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This research is motivated by the application of online learning due to COVID-19, and the lack of available learning media that students can use for independent learning in online learning. This study aims to produce an E - Problem solving based learning module in the electrical machinery course in the electrical engineering department of the Padang State University. This study uses a research and development method with a 4D model. The subjects of this study were students of Diploma Four (D4) 19 electrical engineering at Padang State University. Based on the results of the study obtained the validity of the material with a valid category and media validity obtained with a valid category. The practicality test with lecturer respondents got results in a very practical category and respondents from D4 19 electrical engineering students at the Padang State University stated that E - Problem solving-based learning modules in the electrical machines course were categorized as very practical. So it can be concluded that the E - Problem solving based learning module is valid and practical to use in the lecture process.